Effect of cysteine‐free human fibroblast growth factor‐5s mutant (FGF5sC93S) on hair growth. Issue 6 (18th November 2020) - Kim, Yu Jin; Jung, Narae; Kim, Nayoung; Ha, Jong‐Cheon; Park, Jong Hyeok; Han, Kyuboem; Chang, Minyoul; Lee, Jeunghoon; Kim, Chun‐Hyung
Abstract: Treatment for hair loss is largely limited, and any beneficial effects are often transient. Based on the critical role of the FGF5 isoform, FGF5s, in the hair growth cycle, it may be a good therapeutic candidate for the prevention of hair loss, as well as the promotion of hair growth. To investigate its potential use for hair growth, a mutant form of the FGF5s protein (FGF5sC93S) was generated, expressed, and purified. The FGF5sC93S mutant was able to antagonize FGF5‐induced mitogenic activity, which normally triggers the conversion of hair follicles from the anagen phase to the catagen phase. In addition, the FGF5sC93S mutant efficiently suppressed gene expression induced by FGF5 both human outer root sheath (hORS) and human dermal papilla (hDP) cells. Administration of FGF5sC93S proteins onto the scalps of human subjects significantly increased the total number of hairs at 24 weeks. Together, our data demonstrate that a mutant form of the FGF5s protein could be used as a potential hair promoting agent.